Komunikasi Publik Dalam Pengawasan Peraturan Daerah Lubuklinggau Nomor 12 Tahun 2023 Tentang Pajak Daerah Dan Retribusi Daerah - Andrea Juwi Saputra; Achmad Aminudin; Jatmiko Yogopriyatno (STAI Bumi Silampari, 2026)
Public communication plays a crucial role in ensuring the effectiveness of legislative oversight in the implementation of regional fiscal policies. This study analyzes public communication within the context of the Regional House of Representatives (DPRD) of Lubuklinggau City’s oversight of the implementation of Regional Regulation No. 12 of 2023 concerning Regional Taxes and Levies, from the perspective of policy targets. Employing a descriptive quantitative approach with a survey method, the study involved 88 respondents out of 100 participants in regional legal product oversight activities. Data were collected through a structured questionnaire measuring five dimensions of policy communication based on William N. Dunn’s evaluation criteria: effectiveness, efficiency, adequacy, equity, and responsiveness. The results indicate that public communication in the oversight of the regulation is moderately implemented, with an average score of 2.14 on a 3.00 scale. The dimensions of effectiveness and efficiency show relatively strong performance (means of 2.31 and 2.28), while adequacy, equity, and responsiveness remain at a moderate level, tending toward underperformance (means of 2.08, 2.01, and 2.03, respectively). These findings suggest the need to strengthen participatory communication mechanisms and enhance transparency in the fiscal policy oversight process to ensure democratic accountability and responsiveness to community needs.